2000
DOI: 10.1002/(sici)1522-2624(200004)163:2<143::aid-jpln143>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Microorganisms, Biomass ATP, and Enzyme Activities in Organic and Mineral Particles of a Long-Term Wastewater Irrigated Soil

Abstract: The aim of the study was to elucidate the spatial distribution of soil microorganisms and enyzme activities in a long‐term wastewater treated soil. Soil was sampled from a plough layer of the Ah horizon of a sandy Haplic Luvisol which was either (1) irrigated with municipal wastewater for almost 100 years, or (2) no more irrigated since 20 years, or (3) never received wastewater. The samples were fractionated by wet sieving to obtain seven size fractions of organic and mineral soil particles, and a separate si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…An increase of soil organic matter content through wastewater irrigation has also been reported by others (53)(54)(55)(56)(57)(58). This results in a rising microbial biomass and microbial activity (53,(59)(60)(61). Furthermore, the increased water supply by wastewater irrigation in the dry season seems to provide better conditions for microbial proliferation (53).…”
Section: Resultsmentioning
confidence: 99%
“…An increase of soil organic matter content through wastewater irrigation has also been reported by others (53)(54)(55)(56)(57)(58). This results in a rising microbial biomass and microbial activity (53,(59)(60)(61). Furthermore, the increased water supply by wastewater irrigation in the dry season seems to provide better conditions for microbial proliferation (53).…”
Section: Resultsmentioning
confidence: 99%
“…Many countries are turning to wastewater recycling in order to meet these increased freshwater demands (3)(4)(5). Therefore, planned and managed reuse of wastewater is increasingly practiced not only in arid or semiarid regions but also in temperate and subtropical regions that do not routinely face water shortages (6)(7)(8)(9).…”
mentioning
confidence: 95%
“…Most notably, land application of TWW has the potential to transfer heavy metals (14), pharmaceuticals (15), and even pathogens (16) in the environment and into the food chain (17). In fact, several studies have shown that nutrients, including total carbon (TC), total nitrogen (TN), and soil microbial quotient (the ratio of microbial biomass carbon [MBC] to soil total organic C) remain higher in soils irrigated (IR) with TWW (4,5,9,18,19). Among the nutrients originating from land application of wastewater, nitrate (NO 3 Ϫ ) is considered to be a ubiquitous contaminant worldwide (20, 21), threatening aquatic ecosystems and subsurface aquifers, which are often the major source of potable water.…”
mentioning
confidence: 99%
“…Ammonium, the result of N 2 -fixation is oxidized to NO 3 − and this NH 4 + formation and oxidation to nitrate depends on altitudinal-latitudinal allocation gradients of leaf and root litter, fertilizer-excrement distributions, seasonality, length of dormant periods, microclimate (freeze-thaw cycles, precipitation, solar radiation), O 2 availability, microbial conversion activities, NH 4 + -release, NH 4 + biomass-humus-clay binding, spatially-temporally occurring vegetation-food web interactions, viral shunts, biomass burning and industry contributions, and denitrifier/nitrate ammonifier community activities returning the NH 4 + introduced by N 2 -fixation as NO, N 2 O, N 2 , or NH 3 back to the atmosphere from where it came (Figs. 2, 3, and 4;Scherer 1993;Benckiser 1997;Filip et al 2000;Benckiser and Bamforth 2011;Nacry et al 2013). A prerequisite for NO 3 − formation is a good O 2 availability, while the NO 3 − returning denitrification process as the honeydew sapping and, aphid protecting ant Soil-virus-planttransmitting insect network Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A prerequisite for NO 3 − formation is a good O 2 availability, while the NO 3 − returning denitrification process as the honeydew sapping and, aphid protecting ant Soil-virus-planttransmitting insect network Fig. 2 Nitrogen cycle in terrestrial and aquatic ecosystems (Arcand et al 2013;Flasconaro et al 2013;Benckiser et al 2015) succeeding anaerobic respirations and fermentations are blocked in presence of O 2 . In soil crumbs with their aerobicanaerobic gradients, all oxidizing and reducing activities occur simultaneously and thus the resulting gaseous emissions collected in soil covers are mean values of all aerobic and anaerobic soil processes (Benckiser et al 1984;Klüber and Conrad 1998;Trost et al 2013).…”
Section: Introductionmentioning
confidence: 99%